2021
DOI: 10.1002/its2.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fungicides on creeping bentgrass health and rooting characteristics under abiotic stress

Abstract: Positive effects on plant health provided by quinone outside inhibitors (QoI) and other fungicide classes have been previously reported in turfgrass and other agricultural crops. However, most of the research was conducted under controlled environmental rather than field conditions. Two field and one greenhouse experiments were conducted and repeated in southern California from 2011-2013 to test the ability of selected fungicides to retain or improve creeping bentgrass (Agrostis stolonifera L.; CBG) quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that the strobilurin group of fungicides, in addition to their antifungal activities, can modulate plant physiology and biochemistry [ 32 ]. According to Schiavon et al, (2021) [ 33 ], the positive effects on plants include an increase in chlorophyll content, photosynthetic activity, stomatal aperture, water consumption, plant antioxidant activity, etc. In blackcurrant plants under applications of pyraclostrobin and strobilurin, an increase in phenolic compound concentrations has been reported [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the strobilurin group of fungicides, in addition to their antifungal activities, can modulate plant physiology and biochemistry [ 32 ]. According to Schiavon et al, (2021) [ 33 ], the positive effects on plants include an increase in chlorophyll content, photosynthetic activity, stomatal aperture, water consumption, plant antioxidant activity, etc. In blackcurrant plants under applications of pyraclostrobin and strobilurin, an increase in phenolic compound concentrations has been reported [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Fritz et al. (2022), plant metabolism could be improved after application of this strobilurin fungicide, via an increase in chlorophyll content, photosynthetic activity, stomatal aperture, water consumption, plant antioxidant activity, accumulation of phenolic compounds as flavonols and hydrocinnamic acids, and so forth (Fritz et al., 2022; Schiavon et al., 2021). This observation was reversed in the M treatments, in which plant SDW and RDW were significantly lower when azoxystrobin was introduced to the culture substrate compared to the absence of the fungicide.…”
Section: Discussionmentioning
confidence: 77%
“…Finally, the active compounds of the extracts are related to the physiological and biochemical responses of the plants, and some of the positive effects on plants include increased photosynthetic activity, consumption and efficient use of water, and antioxidant capacity, among others [ 36 ]. However, the application time had a similar trend to the difference in extracts; the shorter application time correlated with the antioxidant capacity, and as the time increased, it correlated with the photosynthetic parameters.…”
Section: Discussionmentioning
confidence: 99%